LEGAL PROTECTION OF NON-MUSLIM WAKAF IN A MULTICULTURAL SOCIETY: AN ISLAMIC LEGAL PERSPECTIVE UTILIZING THE MASLAHAH APPROACH IN MANADO CITY - Nenden Herawaty Suleman; Suprijati Sarib; Moh. Hidayatullah A.K Husein; Moh. Rafiq Soleman (Academic Bright Collaboration, 2026)
This study aims to analyze legal protection for non-Muslim waqf practices in the multicultural community of Manado City through an Islamic legal perspective based on the principle of maslahah. This study also examines the role of the Waqf Deed Official (PPAIW) in the multicultural transformation of waqf land registration. This research uses a qualitative case study approach with juridical-normative and empirical methods. Data were collected through document analysis, in-depth interviews, participant observation, and focus group discussions involving PPAIW, nazhir (Islamic legal adviser), religious leaders, and land office officials in Manado. The research indicates that the principle of maslahah provides flexibility in interpreting non-Muslim waqf as a form of social contribution that supports public welfare and interfaith harmony. However, normative differences among Islamic scholars regarding the legality of non-Muslim waqf remain a challenge. The study also identified a significant gap between national waqf policy and local implementation, reflected in the low percentage of waqf land certified. Despite these limitations, PPAIW demonstrates adaptive capacity in bridging Islamic law, state regulations, and local cultural values. This research contributes to the development of a more adaptive and inclusive waqf legal framework in multicultural societies. However, this research is limited to the local context of Manado City and may not be fully representative of other multicultural regions in Indonesia. This study offers a new perspective on integrating the principle of maslahah with multicultural realities in waqf administration, highlighting the strategic role of PPAIW in promoting inclusive and socially responsive waqf governance in Indonesia.